Drug interactions between opioids and antiretroviral medications: interaction between methadone, LAAM, and delavirdine. - McCance-Katz, Elinore F; Rainey, Petrie M; Smith, Patrick; Morse, Gene D; Friedland, Gerald; Boyarsky, Beth; Gourevitch, Marc; Jatlow, Peter (The American journal on addictions / American Academy of Psychiatrists in Alcoholism and Addictions, 2006)
Understanding the drug interactions between antiretrovirals and opioid therapies may decrease toxicities and enhance adherence with improved HIV outcomes in opioid-dependent individuals. The authors report the results of a clinical pharmacology study designed to determine whether significant pharmacokinetic and/or pharmacodynamic interactions occur between the non-nucleoside reverse transcriptase inhibitor, delavirdine (DLV), and either methadone or levo-alpha acetyl methadol (LAAM) (n = 40). DLV significantly decreased methadone clearance (p = .018) and increased the methadone elimination half-life (p < .001) with a resultant increase in AUC of 19% and C(min)of 29%. The combined effect of DLV on the total concentration of LAAM and its active metabolites, norLAAM and dinorLAAM, was to significantly increase AUC by 43% (p < .001), C(max) by 30% (p = .013), and C(min) by 59% (p = .004) while decreasing T(max) (p = .05). Cognitive deficits over the seven-day study period as measured by the Mini-Mental State Examination, opioid withdrawal symptoms as measured by the Objective Opioid Withdrawal Scale, or complaints of adverse symptoms were not observed. Methadone and LAAM did not affect DLV concentrations. The findings from this study show that DLV treatment in methadone- or LAAM-maintained individuals results in altered opioid pharmacokinetics with an increased exposure and potential risk for opioid toxicity with methadone or LAAM treatment and an increased risk of cardiac toxicity with concomitant LAAM and DLV administration.
Keywords: Adult; Delavirdine; Female; Half-Life; HIV Infections; HIV-1; Humans; Male; Metabolic Clearance Rate; Methadone; Methadyl Acetate; Middle Aged; Opioid-Related Disorders; Reverse Transcriptase Inhibitors; Risk Factors